High angiogenic potential in an in vivo rat corneal model is associated with shorter disease-free survival in low-grade oligodendrogliomas - BOZKURT, SÜHEYLA (ELSEVIER SCI LTD, 2011)
This study aimed to examine the association between time to tumor recurrence, angiogenic potential and tumor contrast-enhancement. Tumor samples were taken from 20 patients with low-grade oligodendroglioma and examined for their angiogenic potential using an in vivo rat corneal model of angiogenesis. Patients were evaluated for tumor contrast enhancement prior to surgical excision using MRI and they were followed for tumor recurrence. Patients who had tumors without contrast enhancement had longer disease-free survival (median time to tumor recurrence, 72 months) compared to those who had tumors with contrast enhancement (median, 42 months: p = 0.0068). Based on corneal angiogenesis assay results, a high angiogenic potential was associated with a significantly shorter disease-free survival. Our findings suggest that radiological contrast enhancement and a high angiogenic potential based on an in vivo corneal angiogenesis assay were related to a shorter disease-free survival. This might have important prognostic implications in patients with low-grade oligodendrogliomas. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Angiogenesis; Oligodendroglioma; Prognosis; Rat corneal angiogenesis assay; Time to tumor recurrence; TUMOR ANGIOGENESIS; GROWTH-FACTOR; THERAPEUTIC TARGET; GLIOMAS; RECURRENCE; ENHANCEMENT; SYSTEM; HEALTH; ASSAYS